ELEMENTARY SCHOOL STUDENTS' ERRORS IN SOLVING WORD PROBLEMS BASED ON NEWMAN ERROR ANALYSIS - Hesty Dian Prasetyaningrum; Mohammad Faizal Amir; Mahardika Darmawan Kusuma Wardana (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Based on previous studies, elementary school students often experience errors in solving word problems on cube and block material. Confirmed Newman Error Analysis (NEA) can analyze the location of student errors in solving word problems. Hence, the purpose of this study was to analyze the errors made by students in solving word problems based on NEA. The type of research used is qualitative research with case studies. The research subjects were 34 students of grade five elementary students with data collection techniques, including tests, interview sheets, and documentation. Data analysis using NEA consists of five stages: reading, comprehension, transformation, process skills, and encoding. From the study results, reading errors were 12,74%, comprehension errors were 51,96%, transformation errors were 9,8%, process skills errors were 52,94%, and encoding errors were 67,64% of students. These errors are caused because students do not read and understand the questions, do not know the formulas and arithmetic operations model used, and count errors.